T242. THE TIMING OF FIRST HELP-SEEKING ATTEMPT IN FIRST EPISODE PSYCHOSIS CAN LEAD TO AVERSIVE PATHWAYS TO CARE. RESULTS FROM THE STEP-ED STUDY. (18th May 2020) - Ferrara, Maria; Guloksuz, Sinan; Mathis, Walter; Raballo, Andrea; Li, Fangyong; Lin, I-Hsin; Syed, Sumaiyah; Gallagher, Keith; Woods, Scott; Tek, Cenk; Srihari, Vinod
Abstract: Background: In the U.S., individuals affected by a first episode psychosis endure 74 mean weeks of delay in receiving effective treatment. Facilitating their access to care has become a public health priority. This delay has proven to have adverse consequences both in short and long-term outcomes. Moreover, aversive pathways to care can imperil subsequent engagement with treatment. A better understanding of how a patient's characteristics might influence interactions with healthcare systems could help tailor early detection interventions and target delays in treatments. By comparing the timing of the first help seeking attempt initiated in a sample of first episode psychosis participants of an early detection campaign, we aim to investigate if people starting to seek help before psychosis will have shorter delays to care, and if an earlier help-seeking attempt correlates with a lower rate of adverse pathways to care (e.g. police involvement, involuntary admissions). Methods: Participants were recruited starting February 1st, 2014 to January 31st, 2019, to STEP, a Coordinated Specialty Care Program in New Haven, CT. Based on the date of the first help-seeking episode, demographic, clinical, and socioeconomic data were used to compare participants who had their first help-seeking attempt before or after psychosis onset (psychosis onset defined using the POPS criteria at the SIPS Interview). Chi-square test was used to compare categorical variables; non-parametric or Student's t test was used to compare the continuous variables. Results: The sample comprised 168 subjects, the majority of which were male, African American, young adults (mean age was 22.4, SD=3.8), with a median time from psychosis onset to first antipsychotic of 52 days [IQ range, 15 – 196], and had their first help-seeking attempt after psychosis onset (70%). Between the two groups there was no difference in sociodemographic characteristics, in psychosis diagnosis, and in the global assessment of functioning (at baseline and 12 months prior). Help-seeking attempts made before psychosis onset were mostly initiated by the patients themselves, while attempts made after onset had the family as the prime initiator. Once the first help-seeking attempt was initiated, it took longer to get prescribed an antipsychotic for subjects seeking help before onset compared to those who sought help after (median 245 days [5 – 1400] vs. 1 day [0 – 999], p<0.0001). By contrast, it took less time for those who sought help before POPS to have their first antipsychotic prescribed once they became psychotic (median 21 days [0 – 445] vs. 56 days [0 – 1153], p=0.03). However, both groups had no significant difference in delay to STEP (p=0.30). Help-seekers after psychosis onset had a trend of longer patient side delay (defined as the time interval from when patients noticed a change-patient's term for psychotic symptoms- to the day they sought help) compared to participants seeking help before onset (median 75 days [0 – 3928] vs. 14 days [0 – 1093], p=0.09). Compared to those who had their first help seeking episode before psychosis onset, the group who sought help after onset had more contacts with the police (64 vs 10), more involuntary admissions (40 vs 6), and same median number of nights spent in a psychiatric hospital six months before STEP enrollment (n=14). Discussion: Timing of first help seeking in early psychosis can be crucial in shaping the individual experience of care. Longer delays in receiving the appropriate treatment and aversive pathways might be associated with help seeking which started only after psychosis onset, compared to first help seeking started before psychosis onset. Tailored interventions are needed to improve psychosis detection and referral of first episodes to specialized services.